Last updated at Dec. 8, 2016 by Teachoo

Transcript

Ex 10.3, 7 Evaluate the product (3 𝑎 − 5 𝑏) ⋅ (2 𝑎 + 7 𝑏). (3 𝑎 − 5 𝑏) ⋅ (2 𝑎 + 7 𝑏) = 3 𝑎 . 2 𝑎 + 3 𝑎.7 𝑏 − 5 𝑏.2 𝑎 − 5 𝑏. 7 𝑏 = 6( 𝑎. 𝑎) + 21( 𝑎. 𝑏) − 10 ( 𝒃. 𝒂) − 35 ( 𝑏. 𝑏) = 6( 𝑎. 𝑎) + 21( 𝑎. 𝑏) − 10 ( 𝒂. 𝒃) − 35 ( 𝑏. 𝑏) = 6( 𝒂. 𝒂) + 11 ( 𝑎. 𝑏) −35 ( 𝒃. 𝒃) = 6 𝒂2 + 11( 𝑎. 𝑏) − 35 𝒃2 Therefore, (3 𝑎 − 5 𝑏) ⋅ (2 𝑎 + 7 𝑏) = 6 𝒂2 + 11 ( 𝒂. 𝒃) − 35 𝒃2

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 8 years. He provides courses for Maths and Science at Teachoo. You can check his NCERT Solutions from Class 6 to 12.